An approach of bio-inspired generalized shape for writer identification - Muda , Azah Kamilah; Shamsuddin, Siti Mariyam (2006)
Writer identification is one of the areas that attract many researchers to work in. It has being focus in forensic and biometric application where the writing styles can be used as biometric features for authenticating an identity. The individualistic of handwriting styles can be adopted into bio-inspired generalized global shape in writer identification. This paper is discussed the problem overview and solution concept of generalized global shape in writer identification. Moreover, to explore the feasibility of this generalized global shape approach in this domain. An experiment based on the proposed framework has been conducted to proof the feasibility of this approach in off-line writer identification.